2022
DOI: 10.1001/jamapediatrics.2021.5698
|View full text |Cite
|
Sign up to set email alerts
|

School Learning Format and Children’s Behavioral Health During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has interrupted the education of more than 1 billion children worldwide, with many experiencing shifts between remote, hybrid, and in-person learning. 1 As the COVID-19 pandemic and interruptions to learning continue, we need to understand their conseq u e n c e s f o r c h i l d r e n's behavioral health to inform response efforts. We used longitudinal data to examine how children's behavioral wellbeing differed by learning format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 3 publications
4
20
0
1
Order By: Relevance
“…The COVID‐19 pandemic has not only interrupted the education of more than 1 billion children worldwide. Beyond learning deficits resulting from school closure, psychologists observed that that children’s behavioural outcomes tended to be worse during remote schooling than during in‐person schooling while hybrid learning fell in between (Hanno et al ., 2021 ). A review of the literature revealed higher screen time and greater social media use, resulting in lower physical activity.…”
Section: Collateral Damagementioning
confidence: 99%
“…The COVID‐19 pandemic has not only interrupted the education of more than 1 billion children worldwide. Beyond learning deficits resulting from school closure, psychologists observed that that children’s behavioural outcomes tended to be worse during remote schooling than during in‐person schooling while hybrid learning fell in between (Hanno et al ., 2021 ). A review of the literature revealed higher screen time and greater social media use, resulting in lower physical activity.…”
Section: Collateral Damagementioning
confidence: 99%
“…Finalmente, todo esto se resume en que la cantidad de horas lectivas y el tiempo dedicado para actividades remotas (tareas, conexión en línea, entre otras) puede tener una diferencia hasta cinco veces, lo que en suma produce una divergencia exponencial e irrecuperable, siendo los grupos vulnerables los grandes damnificados [45][46][47][48] .…”
Section: Meso-nivelunclassified
“…In a sample of Spanish children, around 40% exhibited more frequent problems in cognitive exibility and emotional regulation EF domains (Lavigne-Cerván et al, 2021a), that were best explained by their state anxiety scores. In addition, different studies showed that the incidence of EF di culties was signi cantly associated with the school learning format during the pandemic, with the worse outcomes observed for remote vs inperson schooling (Lavigne-Cerván et al, 2021b; Hanno et al, 2022). Another line of evidence showed that parental distress was an additional predictor of childrens' behavioral EF outcomes (Polizzi et al, 2021).…”
Section: Children's Ef DI Culties During Covid-19 Lockdownmentioning
confidence: 99%
“…). Some of them found worse EF ratings associated with remote schooling (Hanno et al, 2022), or con nement (Lavigne-Cerván et al, 2021a). Children's anxiety (Lavigne-Cerván et al, 2021b) and parental distress (Polizzi et al, 2021) were additional predictors of EF issues.…”
Section: Introductionmentioning
confidence: 99%